PRIVACY AND SECURITY IN DIGITAL COMMUNICATIONS: CHALLENGES AND SOLUTIONS IN CYBERSPACE - Gunawan Widjaja (Prosiding Seminar Nasional Indonesia, 2025)
Privacy and security are two crucial issues in the era of digital communication. The rapid development of technology has created various challenges in protecting personal information and maintaining security in cyberspace. The main challenges faced in digital communication include identity theft, data breaches, cyber attacks, and misuse of personal information. Solutions include the use of encryption, security software, education and awareness raising, regulation and enforcement, and individual responsibility. Therefore, it is important to emphasise the collective efforts and constant vigilance of various parties, including individuals, companies, and governments, to create a safer and more trusted digital environment. With a comprehensive and adaptive approach to technological developments, it is expected to protect privacy rights, reduce the risk of cyber threats, and promote sustainable growth of the digital economy.